2020
DOI: 10.1073/pnas.2011221117
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 detection using isothermal amplification and a rapid, inexpensive protocol for sample inactivation and purification

Abstract: The current severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has had an enormous impact on society worldwide, threatening the lives and livelihoods of many. The effects will continue to grow and worsen if economies begin to open without the proper precautions, including expanded diagnostic capabilities. To address this need for increased testing, we have developed a sensitive reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay compatible with current reagents, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
362
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(373 citation statements)
references
References 23 publications
11
362
0
Order By: Relevance
“…Next, we compared the Gene-N-A, Color-N, Color-E, and Color-N/E combination to second-generation primers described in Zhang et al [22] (Gene-N2, Gene-E1 and As1e). We found that As1e, originally published by Rabe et al [29], yielded the lowest Cq value followed closely by a combination of As1e with the two primers targeting the Gene-N2 and Gene-E1 genes designed by Zhang et al (Fig 3B). The Color-N primer yielded similar Cq values to the triple combination primer set from Zhang et al We also tested the Color-N, Color-E1, and Gene-N-A gene primer sets against additional published primers that target ORF1a (Lamb, Yu, El-Tholoth, and Zhang primers) either alone or in combination and compared them to the Gene-N-A gene primer set (S1 Table).…”
Section: Alternative Primers Improve Efficiencysupporting
confidence: 61%
See 2 more Smart Citations
“…Next, we compared the Gene-N-A, Color-N, Color-E, and Color-N/E combination to second-generation primers described in Zhang et al [22] (Gene-N2, Gene-E1 and As1e). We found that As1e, originally published by Rabe et al [29], yielded the lowest Cq value followed closely by a combination of As1e with the two primers targeting the Gene-N2 and Gene-E1 genes designed by Zhang et al (Fig 3B). The Color-N primer yielded similar Cq values to the triple combination primer set from Zhang et al We also tested the Color-N, Color-E1, and Gene-N-A gene primer sets against additional published primers that target ORF1a (Lamb, Yu, El-Tholoth, and Zhang primers) either alone or in combination and compared them to the Gene-N-A gene primer set (S1 Table).…”
Section: Alternative Primers Improve Efficiencysupporting
confidence: 61%
“…We used fluorescent-based detection with Warmstart LAMP reagents and the included fluorescent dye (New England Biolabs, NEB cat # E1700L). We tested primer sets developed in previous studies targeting several SARS-CoV-2 genes as shown in S1 Table [13,14,22,[29][30][31][32][33]. Of note, the Color-Orf1a primers and Lamb-Orf1a primers are identical but were used at different concentrations per the protocols developed by each originating lab.…”
Section: Rt-lampmentioning
confidence: 99%
See 1 more Smart Citation
“…RPA has potential advantages over other isothermal amplification technologies such as loop-mediated isothermal amplification (LAMP) 13 as it can be performed near ambient temperature (37-42°C) and is more rapid. While several creative applications of LAMP technologies to diagnose COVID-19, the disease caused by SARS-CoV-2, have recently been developed and show promise [14][15][16][17][18] , RT-RPA has been less explored.…”
mentioning
confidence: 99%
“…We envisioned jLAMP assay workflow as displayed in Figure 3a, where heat treated swab media or saliva is directly added to the jLAMP master mix, heated at 60 °C and read out visually. First, we screened several sets of LAMP primers [8][9][10] to achieve optimum performance and found that those designed by D. Wang 10 yielded the best sensitivity. We also designed primers specific for the human RPP30 and 18S rRNA genes to be used to test sample integrity.…”
Section: Lamp Primers and Reaction Optimization Having Established Tmentioning
confidence: 99%